Air Sampling and Industrial Hygiene Engineering - Boss, Martha J. (CRC Press, 2009)
We know certain chemicals cause problems in the workplace. The issues now are: Where do they occur in the workplace? How can we best evaluate them? What are the procedures for dealing with them safely? Many books simply define the problem and tell you that you need a program. Air Sampling and Industrial Hygiene gives you a guide to air sampling protocols from start to finish.